Audio culture : readings in modern music - Cox, Christoph, 1965-; Warner, Daniel, 1954- (Bloomsbury Academic, an imprint of Bloomsbury Publishing Inc, 2017)
The groundbreaking Audio Culture: Readings in modern music (Continuum; September 2004; paperback original) maps the aural and discursive terrain of vanguard music today. Rather than offering a history of contemporary music, Audio culture traces the genealogy of current musical practices and theoretical concerns, drawing lines of connection between recent musical production and earlier moments of sonic experimentation. It aims to foreground the various rewirings of musical composition and performance that have taken place in the past few decades and to provide a critical and theoretical language for this new audio culture.This new and expanded edition of the Audio culture contains twenty-five additional essays, including four newly-commissioned pieces. Taken as a whole, the book explores the interconnections among such forms as minimalism, indeterminacy, musique concrète, free improvisation, experimental music, avant-rock, dub reggae, ambient music, hip hop, and techno via writings by philosophers, cultural theorists, and composers. Instead of focusing on some "crossover" between "high art" and "popular culture," Audio culture takes all these musics as experimental practices on par with, and linked to, one another. While cultural studies has tended to look at music (primarily popular music) from a sociological perspective, the concern here is philosophical, musical, and historical. Audio culture includes writing by some of the most important musical thinkers of the past half-century, among them John Cage, Brian Eno, Ornette Coleman, Pauline Oliveros, Maryanne Amacher, Glenn Gould, Umberto Eco, Jacques Attali, Simon Reynolds, Eliane Radigue, David Toop, John Zorn, Karlheinz Stockhausen, and many others. Each essay has its own short introduction, helping the reader to place the essay within musical, historical, and conceptual contexts, and the volume concludes with a glossary, a timeline, and an extensive discography.